Effects of Nanosecond Pulsed Electric Fields in Cell Vitality, Apoptosis, and Proliferation of TPC-1 Cells - Zhenguo Liu; Yawen Zou; Ying Sun; Xiaolong Chen; Xinhua Chen; Zhigang Ren (Analytical Cellular Pathology)
Objective. To evaluate the effects of nanosecond pulsed electric fields (nsPEFs) with different pulse durations in cell vitality, apoptosis, and proliferation of TPC-1 cells, optimize pulse parameters and expand the application range of nsPEFs. Methods. The pulse duration of 0, 300 ns, 500 ns, and 900 ns is generated with nsPEF generator. CCK-8 was used to investigate the effect of nsPEFs on the viability of TPC-1 cells. Flow cytometry was used to evaluate the apoptosis of TPC-1 after pulse treatment. The effect of nsPEFs on the proliferation ability of TPC-1 cells was detected by 5-ethy-nyl-2′-deoxyuridine. The morphological changes of TPC-1 cells after pulse treatment were observed by transmission electron microscopy. Results. NsPEFs with 900 ns pulse duration can significantly affect the viability of TPC-1 cells and inhibit the proliferation ability of TPC-1 cells. In addition, nsPEFs can also induce apoptosis of TPC-1 cells. Conclusion. NsPEFs with longer pulse duration can significantly affect the biological behavior of TPC-1 cells, such as cell viability and proliferation ability, and can also induce cell apoptosis, thereby inhibiting cell growth.